Study of Milk Yield and Some of Its Chemical Components and Its Relationship with Lambs Growth of Awassi Sheep - Abdullah, Muthanna Fathi (Journal of agricultural, environmental and veterinary sciences, 2023)
Data were analyzed from of two flocks of Awassi sheep. The first flock belongs to the College of Agriculture and Forestry, Mosul University, and the second flock belongs to Animal Breeding Station, Mosul (Al-Rashedia) which conducted on 799 and 802 records of ewes and born lambs were recorded during two seasons 2009-2010. The results revealed highly significant (P
Keywords: Awassi Sheep; Lamb Growth; Milk yield and components; SCC